Law Enforcement Against Adult Child Mobbing - Fahrezi, Rachman; Algonim, Fadhel; Saputra, Gilang; Sanusi, Sanusi; Nurhaqi, Ari (Devotion : Journal of Research and Community Service, 2024)
In general, mobbing is carried out by children against adults, but on the contrary mobbing is carried out by adults against children. The raid caused minor injuries and trauma to the child as a victim. Raids are included in the criminal act of persecution that must not be allowed and must be carried out by law enforcement. This study aims to analyze the law enforcement process against the criminal act of adult mobbing on children carried out by the Gempol Palimanan Sector Police of Cirebon Regency to the process at the Sumber Prosecutor's Office of Cirebon Regency. The type of research used qualitative research with a descriptive approach to analysis that describes and analyzes facts or data that exist and are collected when conducting research, research methods used empirical juridical or sociological, namely through interviews or interviews with related parties, police, perpetrators, victims and prosecutors. Based on the analysis, it was found that Gempol Police conducted law enforcement assisted by the victim's family in arresting the perpetrators, not all perpetrators were caught. Only one was caught and law enforcement proceedings were carried out. The law enforcement process continues to the Source Prosecutor's Office, the perpetrator asks for a resolution to be carried out by Restorative Justice at the Source Prosecutor's Office. Settlement through Restorative Justice is also agreed upon by the victim. For the sake of justice, Gempol Police should also process other perpetrators of mobbing, if possible, Restorative Justice is carried out in investigations and investigations at the police.